Integrasi AHP dan QFD dalam Penentuan Kualitas Bahan Baku Ayam untuk Mitigasi Risiko Supply Chain - Silvana Mohamad; Moh. Ainul Fais; Sofiyanurriyanti Sofiyanurriyanti; Abdul Rasyid (Jurnal Optimalisasi, 2026)
This study aims to determine the priority of chicken raw material quality risks and formulate technical responses to support supply chain risk mitigation in restaurant operations. The research object was Restoran XYZ, Surabaya, which relies on chicken as its main raw material. This study used an integrated Analytic Hierarchy Process (AHP) and Quality Function Deployment (QFD) approach. Primary data were collected through observation, interviews, and questionnaires involving restaurant stakeholders responsible for procurement, inspection, and processing of chicken raw materials. AHP was used to determine supply chain risk priorities, while QFD was used to translate quality attributes into technical responses through the House of Quality matrix. The AHP results show that the highest priority risk was chicken quality not meeting standards, with a weight of 0.422, followed by delayed delivery at 0.254, price mismatch at 0.162, inaccurate weighing at 0.104, and quantity mismatch at 0.059. The inconsistency ratio was 0.09, indicating acceptable pairwise comparisons. The QFD results show that the main quality attributes were chicken freshness, followed by feather cleanliness, cutting condition, and chicken weight. The main technical responses were worker training at 26.87%, rechecking weighing results at 22.39%, preparing delivery invoices at 22.39%, careful weighing at 17.91%, and scheduling raw material delivery at 10.45%. These findings show that integrating AHP and QFD can support structured decision-making by linking risk priorities with operational quality improvement. The results can be used to develop standard operating procedures for raw material acceptance, supplier evaluation, and supply chain risk mitigation.